Central catecholamine metabolism in vivo and the cognitive and motor deficits in Parkinson's disease. Issue 10 (October 1983) - Mann, J J; Stanley, M; Kaplan, R D; Sweeney, J; Neophytides, A
Abstract : Cerebrospinal fluid levels of homovanillic acid (HVA) in unmedicated patients with Parkinson's disease were 45% of levels in control subjects. Levels of 3-methoxy-4-hydroxyphenylglycol (MHPG) and platelet monoamine oxidase activity (MAO) did not differ. Within the Parkinson's disease group platelet MAO B activity correlated with HVA (an MAO B substrate) but not MHPG (an MAO A substrate). A mild global dementia was found that did not correlate with the more severe motor deficit. There was a negative correlation between the motor deficit and HVA levels but not with MHPG. Cognitive functioning correlated positively with platelet MAO, and the ratio of HVA to MHPG levels and negatively with MHPG alone. It is postulated that dopaminergic and noradrenergic activity or the functional balance between these systems may contribute to the observed cognitive dysfunction.